(untitled) (Delta Medical College Journal, 2015)
Background: As hypofractionated radiotherapy for post-operative breast cancer patients safe, effective and more convenient, it might be beneficial for patients of developing countries like ours. Objective: This study was done to evaluate the safety and efficacy of hypofractionated whole breast radiation therapy in patients who underwent breast conserving surgery and hypofractionated radiation therapy in patients who underwent mastectomy and axillary clearance. Materials and method: This cross sectional study was conducted in Delta Hospital Ltd, Dhaka, Bangladesh, including 50 postoperative patients, (12 patients in Breast Conservation Therapy group and 38 in Post Mastectomy Radiation Therapy group), with invasive ductal carcinoma of breast treated with this hypofractionated radiotherapy protocol during the last 1.5 year. The patients were treated with 3DCRT, LINAC, 6 MV photon and appropriate electron energy. Results: Minimal post treatment acute morbidity was observed. Forty seven patients (94%) had grade-I acute skin toxicity and only 3 patients (6%) developed grade-II acute skin toxicity. Conclusion: Hypofractionated radiotherapy is as safe and effective as conventional fractionated radiotherapy and superior in terms of convenience. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22232 Delta Med Col J. Jan 2015; 3(1): 04-08